Floristic composition and diversity of mangroves in selected sites in the Province of Iloilo, Panay Island, Philippines. - Madas, Christy Suarez
Mangroves is considered as one of the richest ecosystem in tropical areas. Its floral composition and diversity are gradually declining due to constant and countless pressures and disturbances caused by humans and the environment as well. However, there have been minimal studies on the floral composition of these areas in the Province of Iloilo. Thus, this study was conducted to assess the floristic composition and diversity of mangroves in the province of Iloilo using transect and ocular survey method in selected municipalities in the Iloilo Province Mangrove diversity in the province is high having 29 species of 16 genera from 14 families. These are: Acanthus ebracteatus, Acanthus ilicifolius and Acanthus volubilis (Family Acanthaceae); Avicennia marina, Avicennia officinalis and Avicennia rumphiana (Family Avicenniaceae); Camptostemon philippinensis Family Bombacaceae); Lumnitzera racemosa (Family Combrataceae), Excoecaria agallocha (Family Euphorbiaceae), Pemphis acidula (Lythraceae), Xylocarpus granatum, Xylocarpus moluccensis and Xylocarpus rumphii (Family Meliaceae), Aegiceras corniculatum and AEgiceras floridum (Family Myrsinaceae), Osbornia octodonta (Family Myrtaceae), Nypa fruiticans (Family Palmae), Bruguiera cylindrica, Bruguiera gymnorhiza and Bruguiera sexangula, Ceriops decandra, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata and Rhizophora stylosa (Family Rubiaceae), Sonneratia alba (Family Sonneratiaceae) and Heritiera littoralis (Family Sterculiaceae). The Shannon-Weaver Index of Diversity (H'), commonly used to characterize the species diversity in a community is associated with Pielou's Equitability Index for the evenness of the species present in the same area. Iloilo Province has an index of diversity at H' = 0.62170 and evenness at J' = 0.42512. The index diversity is correlated with the equitability or evenness of the species which means that the diversity of mangrove flora influences the distribution of evenness of the species in the area. On the other hand, individuals of various species were not equal. Some species were more numerous than the others. Among the selected sites, Estancia has 21 species while Barotac Viejo has a relatively low diversity index of 0.46697 (18 species). On the other hand, Ajuy had the highest floral composition with 26 species from 16 genera of 14 families while Tigbauan has the least flora, which is composed only of 9 species. Estancia had the highest diversity of 21 species, index of diversity 0.744, the availability of various types of substrates and variations in geomorphological factors seemingly account for the observed diversity of mangrove species in selected municipalities in the Province of Iloilo.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangroves -- Panay Island, Philippines